Les oratorios bibliques de Haendel ou « ll faut l’entendre pour le croire » - Joël Richard (Revue LISA)
This article contends that, having being denied the possibility of truly staging his biblical oratorios, Handel turned this apparent dramatic void into a truly musical force. Examples taken from Saul, Joshua, Belshazzar, Israel in Egypt and Samson will show how the complex and varied processes of (re)writing the librettos from their original biblical source often provided Handel with literary pauses, or even “blanks”, which he more than fully filled with moments of “pure” musical experimentation: when singing is heard off stage, or when voices are simply heard no more, sounds do become meaning and hearing is truly believing.